Analisis Foto Dan Video Sebagai Strategi Branding Pempek Di Bandar Lampung - M Farhan; Fina Anggraini; Zahwa Arzetty Yusuf; Purwanto Putra; Zaimasuri Zaimasuri (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze the role of photography and video as a brand strategy for Pempek Bandar Lampung products. As one of South Sumatra's famous culinary specialties, Pempek needs a creative approach to increase the attractiveness and sustainability of the market. In the digital era, visualization is an important component of a brand's consumer perception design. With a qualitative approach, this study analyzes how photos and videos by Pempek entrepreneurs from Bandar Lampung are used to build a strong brand image. This data was collected by observing various visual content on social media and by observing interviews with economic actors. The results of the study show that the use of photos and videos plays an important role in increasing brand awareness and customer loyalty. In addition, a visual strategy that can be proven to be effective in introducing product innovation and consumer attention. The study concluded that the use of visual intensity can be an effective tool to improve the position of Pempek products in regional and regional markets.